Replication of a study : Too sweet to eat: Exploring the effects of cuteness on meat - Vachelová, Kristýna; Houdek, Petr, 1981-; Say, Nicolas; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis explores the psychological mechanisms that influence consumer decisions related to meat consumption, focusing on how the perceived cuteness of animals affects empathy and the willingness to eat meat. Building on previous research by Zickfeld et al. (2018), the study replicates and extends their experimental design within the cultural context of the Czech Republic. A total of 632 participants were randomly assigned to view images of lambs manipulated to appear either cute or neutral. Participants then rated the animal’s cuteness and angriness, we obtained their level of empathy, and willingness to consume lamb. Results confirmed the effectiveness of the cuteness manipulation and showed that participants in the cute condition reported significantly higher empathy than those in the neutral condition. While cuteness did not directly reduce willingness to eat meat, it had a significant indirect effect mediated by empathy. These findings align with previous studies and suggest that emotional responses (particularly empathy) play a crucial role in moral food decision-making. The thesis contributes to growing evidence on the emotional foundations of dietary choices and highlights the potential of using emotional appeals in ethical or sustainability campaigns targeting meat consumption.
Vedoucí práce: Petr Houdek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor bakal. práce]; bakalářské práce; bachelor's theses